Photophysicochemical and Biological Properties of New Phthalocyanines Bearing 4-(trifluoromethoxy)phenoxy and 2-(4-methylthiazol-5-yl)ethoxy Groups on Peripheral Positions - Farajzadeh, Nazli; Ozdemir, Sadin; Gonca, Serpil; Atmaca, Goknur Yasa; Erdogmus, Ali; Bayir, Zehra Altuntas; Kocak, Makbule Burkut (WILEY, 2022)
As thiazoles and fluorinated groups are well known as active species of hybrid pharmaceutical agents, this study aimed to evaluate the synergic effect of these groups on the biological features of phthalocyanines for the first time in the hope of discovering efficient pharmaceutical agents. Therefore, a new phthalonitrile derivative namely 4-(2-(4-methylthiazol-5-yl)ethoxy)-5-(4-(trifluoromethoxy)phenoxy)phthalonitrile (1) and its metal-free (2)/metal phthalocyanines (3-5) were prepared and characterized using various spectroscopic techniques. Solubility of new phthalocyanines (2-5) was examined in a series of polar and nonpolar solvents. Additionally, sono/photochemical methods were applied to examine the photophysical and sono/photochemical properties of new zinc phthalocyanine to measure its potential as a probable material for sono/photodynamic therapies. The antioxidant activities of compounds (1-5) were evaluated using the DPPH scavenging activity method and the highest radical scavenging activity was obtained 92.13% (200 mg L-1) for manganese phthalocyanine. All the phthalocyanines demonstrated high DNA nuclease activity, as well. The antimicrobial activities of compounds (1-5) were investigated using disk diffusion and microdilution methods. The phthalocyanines exhibited effective microbial cell inhibition activity against Escherichia coli (E. coli). Antimicrobial photodynamic therapy activity was investigated against E. coli by LED irradiation. Compounds (2-5) acted as photosynthesizers. Also, they displayed significant biofilm inhibition activity against Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa).
Keywords: SUBSTITUTED SILICON PHTHALOCYANINE; SINGLET OXYGEN EFFICIENCY; PHOTODYNAMIC THERAPY; METAL-FREE; IN-VITRO; ANTIOXIDANT PROPERTIES; SPECTROELECTROCHEMICAL PROPERTIES; ZINC; THIAZOLE; METALLOPHTHALOCYANINES; Biochemistry & Molecular Biology; Biophysics